Arthrogryposis Multiplex Congenita: Multiple Congenital Joint Contractures - Hamza Sucuoglu; Nurettin Irem Ornek; Cagkan Caglar (Case Reports in Medicine)
Arthrogryposis multiplex congenita (AMC) is a syndrome characterized by nonprogressive multiple congenital joint contractures. The etiology of disease is multifactorial; it is most commonly suspected from absent fetal movements and genetic defects. AMC affects mainly limbs; also it might present with other organs involvement. It is crucial that the diagnosis of AMC should be kept in mind by musculoskeletal physicians in newborns with multiple joint contractures and patients must begin rehabilitation in early stage after accurate diagnosis in terms of functional independence. We present the diagnosis, types, clinical features, and treatment approaches of this disease in our case with literature reviews.